Exploring impacts of participatory science communication on science, politics, and society - Kirschke, Sabrina; Glahe, Jannis; Kirschke, Dieter (Frontiers in Communication, 2025)
Discussions on potential impacts of participatory science communication (PSC) formats on science, society, and politics would benefit from more empirical investigation. This article provides a systematic analysis of the perceptions of science communicators on the potential impacts of PSC on these different groups. The two basic questions are: What impact does PSC have on science, society, and politics? To what extent can these impacts be attributed to the different PSC communication formats? To answer these questions, 20 PSC projects implemented in the German Science Year 2022 were analysed. Semi-structured interviews with project coordinators revealed diverse potential impacts on science, society, and politics. While the impacts on science and society were predominantly assessed positively, impacts on politics were considered to be more case-specific and subordinate. Regression analyses indicate that these impacts can rarely be attributed to the PSC communication formats applied in projects. The results call into question global statements on the relevance of participation, and highlight the importance of different impact mechanisms for different groups in communication projects.